2023
DOI: 10.1021/acs.est.3c05266
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Urban Ammonia Emissions May Be Substantially Underestimated in Beijing, China

Jiayu Xu,
Mengran Lu,
Yixin Guo
et al.

Abstract: Ammonia (NH 3 ) is critical to the nitrogen cycle and PM 2.5 formation, yet a great deal of uncertainty exists in its urban emission quantifications. Modelunderestimated NH 3 concentrations have been reported for cities, yet few studies have provided an explanation. Here, we explore reasons for severe WRF-Chem model underestimations of NH 3 concentrations in Beijing in August 2018, including simulated gas-particle partitioning, meteorology, regional transport, and emissions, using spatially refined (3 km resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…This will require further observational research on atmospheric NH 3 in urban Beijing in the future. In addition, existing studies have demonstrated that emission inventories have underestimated atmospheric NH 3 emissions in the Beijing urban area (Xu et al, 2023), and the assessment results have varied across emission inventories . Additionally, given the limited research years of current emission inventories, the observed differences between long-term trends in monitored NH 3 concentrations and NH 3 emissions require continued attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This will require further observational research on atmospheric NH 3 in urban Beijing in the future. In addition, existing studies have demonstrated that emission inventories have underestimated atmospheric NH 3 emissions in the Beijing urban area (Xu et al, 2023), and the assessment results have varied across emission inventories . Additionally, given the limited research years of current emission inventories, the observed differences between long-term trends in monitored NH 3 concentrations and NH 3 emissions require continued attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the dominant role of agricultural sources of NH 3 at global or regional scales, recent observations have revealed that NH 3 concentrations are higher in densely populated urban areas that have low agricultural activity. This finding posed a challenge to simulations driven by the current NH 3 emission inventories (EIs), as they could not accurately reproduce the observed high NH 3 concentrations in urban areas. Meanwhile, more and more isotopic source apportionment results pointed out that nonagricultural activities, such as fossil fuel combustion, industrial processes, on-road traffic, , slip from power plants, and waste, presented a larger contribution to atmospheric NH 3 concentration in urban areas as compared to the agricultural sectors. As shown in Table S1, during nonpollution periods, the contribution of nonagricultural sources to atmospheric NH 3 concentrations in the regions across China varied from 14 to 76%, and these values even reached 49–97% during haze periods. However, the relative contributions of nonagricultural and agricultural sources to the total NH 3 emissions from the isotopic source apportionment results significantly differed from those derived from the bottom-up anthropogenic NH 3 EIs (e.g., the Multi-resolution Emission Inventory for China, MEIC) at the city level (Figure S1). For instance, isotopic source apportionment revealed that fossil fuel was a significant source of NH 3 at an urban site in Beijing, contributing as much as 76%, whereas the corresponding value was only 35% based on the NH 3 EI .…”
Section: Introductionmentioning
confidence: 99%